The Moderating Effect of Profitability and Leverage on The Influence of Eco-Efficiency on Firm Value - Shinta Nastitie Komalasari; Gustita Arnawati Putri; Yoga Pratama Nugraha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted because of the emergence of cases of environmental pollution due to excessive production activities and the lack of awareness of business actors towards environmental conservation. Since the emergence of COVID-19 in Indonesia, the demand for medicines and other consumer products has increased. Public demand for companies to continue to care about environmental sustainability to reduce the negative impact of company activities on the environment. One concept that can be applied by management to handle problems that occur between the environment and the company is the concept of eco-efficiency. The purpose of this study is to, first, test the effect of eco-efficiency on firm value, second, test the effect of eco-efficiency on firm value with profitability and leverage as moderating variables. The sample of this research is manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2020-2023 using purposive sampling method. This research analysis method uses simple regression analysis and moderating analysis regression (MRA). This study provides evidence that environmental management implemented by the company can significantly provide good company value, besides that the high level of profit earned by the company can moderate the relationship between eco-efficiency and company value with a positive effect but in this study leverage cannot moderate the eco-efficiency relationship.